Perceived norms about male circumcision and personal circumcision status: a crosssectional, population-based study in rural Uganda - Perkins, Jessica M.; Kakuhikire, Bernard; Baguma, Charles; Jeon, Sehee; Walker, Sarah F.; Dongre, Rohit; Kyokunda, Viola; Juliet, Mercy; Satinsky, Emily N.; Comfort, Alison B.; Siedner, Mark; Ashaba, Scholastic; et al. (medRxiv, 2023)
Introduction: Over the past decade, 15 high-priority countries in eastern and southern Africa have promoted voluntary medical male circucmsion for HIV and STI prevention. Despite male circumcision prevalence in Uganda nearly doubling from 26% in 2011 to 43% in 2016, it remained below the target level by 2020. Little is known about perceived norms of male circumcision and their association with circumcision uptake among men. Methods: We conducted a cross-sectional study targeting all adult residents across eight villages in Rwampara District, southwestern Uganda in 2020-2022. We compared what men and women reported as the adult male circumcision prevalence within their village (perceived norm: >50% (most), 10% to <50% (some), <10%, (few), or do not know) to the aggregated prevalence of circumcision as reported by men aged <50 years. We used a modified multivariable Poisson regression model to estimate the association between perceived norms about male circumcision uptake and personal circumcision status among men. Results: Overall, 167 (38%) men < 50 years old were circumcised (and 27% of all men were circumcised). Among all 1566 participants (91% response rate), 189 (27%) men and 177 (20%) women underestimated the male circumcision prevalence, thinking that few men in their own village had been circumcised. Additionally, 10% of men and 25% of women reported not knowing the prevalence. Men who underestimated the prevalence were less likely to be circumcised (aRR = 0.51, 95% CI 0.37 to 0.83) compared to those who thought that some village men were circumcised, adjusting for perceived personal risk of HIV, whether any same household women thought most men were circumcised, and other sociodemographic factors. Conclusions: Across eight villages, a quarter of the population underestimated the local prevalence of male circumcision. Men who underestimated circumcision uptake were less likely to be circumcised. Future research should evaluate norms-based approaches to promoting male circumcision uptake. Strategies may include disseminating messages about the increasing prevalence of adult male circumcision uptake in Uganda and providing personalized normative feedback to men who underestimated local rates about how uptake is greater than they thought.
Keywords: Misperceived norms; Descriptive norms; HIV; STI; Male circumcision; Sexual health